Single-molecule FRET reveals a cooperative effect of two methyl group modifications in the folding of human mitochondrial tRNALys - Kobitski, Andrei Yu.; Hengesbach, Martin; Seidu-Larry, Salifu; Dammertz, Kirsten; Chow, Christine S.; van Aerschot, Arthur; Nienhaus, G. Ulrich; Helm, Mark (Chemistry & biology, 2011)
Using a combination of advanced RNA synthesis techniques and single molecule spectroscopy, the deconvolution of individual contributions of posttranscriptional modifications to the overall folding and stabilization of human mitochondrial tRNALys is described. An unexpected destabilizing effect of two pseudouridines on the native tRNA folding was evidenced. Furthermore, the presence of m2G10 alone does not facilitate the folding of tRNALys, but a stabilization of the biologically functional cloverleaf shape in conjunction with the principal stabilizing component m1A9 exceeds the contribution of m1A alone. This constitutes an unprecedented cooperative effect of two nucleotide modifications in the context of a naturally occurring RNA, which may be of general importance for tRNA structure and help understanding several recently described decay pathways for hypomodified tRNAs.